Investigating The Impact of Watching subtitled Videos on improving EFL students' Vocabulary Knowledge The Case of Second Year EFL Students at Mohamed Cherif Messaadia university ˒Souk- Ahras. - SEHILI, Ryma (My University, 2023)
Abstract This study was set to investigate the effectiveness of using subtitled videos as an authentic audio visual material on the development of language acquisition in general, and vocabulary knowledge in particular. This research has been built on two main hypotheses. Initially, students who learn vocabulary through subtitled videos will be more inclined to improve their vocabulary knowledge. Secondly, the implementation of subtitled videos is an additional tool for students to enrich their vocabulary stock. This descriptive study used a mixed method to collect both qualitative and quantitative data; using a questionnaire comprised of 19 statements was addressed to n40 students chosen from N99 second year students of English, Department of English, Mohamed Cherif Messdia University, Souk-Ahras. In addition to that, a semi-structured interview was conducted with six EFL teachers of Oral Expression & Comprehension subject selected conveniently. Overall, the hypotheses are confirmed. That is, subtitled videos are very helpful in facilitating learners’ vocabulary acquisition, especially for beginners and intermediate levels. ---------------------- الملخص لقد تم تعيين هذه الدراسة للتحقق من فعالية استخدام الفيديوهات المترجمة كأداة سمعية بصرية أصيلة في تطوير مهارات التعلم اللغوي بشكل عام ومعرفة المفردات بشكل خاص. تم بناء هذه الدراسة على فرضيتين رئيسيتين. أولاً، أن الطلاب الذين يتعلمون المفردات من خلال الفيديوهات المترجمة سيكونون أكثر ميلاً لتحسين معرفتهم بالمفردات. ثانياً، أن استخدام الفيديوهات المترجمة يعتبر أداة إضافية لإثراء مخزون المفردات لدى الطلاب. استخدمت هذه الدراسة الوصفية طريقة مختلطة لجمع البيانات الكمية والنوعية، حيث تم توجيه استبيان يتكون من 19 عبارة إلى 40 طالبًا تم اختيارهم من بين 99 طالبًا من قسم اللغة الإنجليزية في جامعة محمد الشريف مساعدية ،سوق اهراس وهم طلاب سنة ثانية في تعلم اللغة الإنجليزية كلغة أجنبية بالإضافة إلى ذلك، تم إجراء مقابلة شبه منظمة مع ستة مدرسين لغة إنجليزية كلغة أجنبية لمادة الصوتيات والاستيعاب الشفوي تم اختيارهم بشكل ملائم. وبشكل عام، تم تأكيد الفرضيات. وهذا يعني أن الفيديوهات التي تحتوي على ترجمة مكتوبة تساعد كثيرًا في تسهيل اكتساب المفردات لدى الطلاب. --------------------- Résumé Cette étude visait à enquêter sur l'efficacité de l'utilisation de vidéos sous-titrées en tant que matériel audiovisuel authentique pour le développement de l'acquisition de langues en général et de la connaissance du vocabulaire en particulier. Cette recherche a été construite sur deux hypothèses principales. Initialement, les étudiants qui apprennent le vocabulaire à travers des vidéos sous-titrées seront plus enclins à améliorer leur connaissance du vocabulaire. Deuxièmement, la mise en œuvre de vidéos sous-titrées est un outil supplémentaire pour permettre aux étudiants d'enrichir leur stock de vocabulaire. Cette étude descriptive a utilisé une méthode mixte pour collecter des données qualitatives et quantitatives; en utilisant un questionnaire composé de 19 déclarations adressées à 40 étudiants choisis parmi les 99 étudiants de deuxième année d'anglais de l'Université de Souk-Ahras. En plus de cela, une interview semi-structurée a été menée auprès de six enseignants d'anglais langue étrangère (EFL) du cours d'Expression et Compréhension Orales, sélectionnés de manière pratique. Dans l'ensemble, les hypothèses sont confirmées. C'est-à-dire que les vidéos sous-titrées sont très utiles pour faciliter l'acquisition de vocabulaire des apprenants, surtout pour les niveaux débutants et intermédiaires.